LED/laser photoactivation enhances the whitening efficacy of low concentration hydrogen peroxide without microstructural enamel changes - Costa, Joatan Lucas de Sousa Gomes; Besegato, João Felipe; Zaniboni, Joissi Ferrari; Kuga, Milton Carlos (Elsevier, 2021)
BACKGROUND: The association of low concentration hydrogen peroxide (HP) and a light source has been widely used to achieve efficient bleaching. We investigated the colorimetric and microstructural changes of bovine enamel bleached with 6% HP associated or not with a hybrid light source system of violet light and laser (LED/laser). METHODS: Twenty bovine crowns were used to obtain specimens of 7 × 7 × 2 mm. Then, they were randomized in two groups (n=10): 6% HP and 6% HP + LED/laser. After staining with dark tea solution, three bleaching sessions were performed. Colorimetric evaluation (∆L*, ∆a*, ∆b*, ∆E00 [CIEDE2000] and WID) after 24 hours of each session and 7 days after the final bleaching session was performed. Enamel Vickers microhardness at baseline, 24 hours and 7 days after the last bleaching session were also evaluated. Two-way repeated measures ANOVA and Bonferroni post-test was used at a significance level of 5%. RESULTS: 6% HP and 6% + HP LED/laser showed satisfactory bleaching results. The group photoactivated showed higher WID values (p<0.05). Differences between groups were observed for ∆E00, ∆L* and ∆a* (p<0.05), except for ∆b* (p>0.05). Intra-group differences were also found (p<0.05). Regarding microhardness, no inter or intra-group differences were observed (p>0.05). CONCLUSIONS: The photoactivation with LED/laser enhanced the whitening efficacy of 6% HP compared to the group without photoactivation. Thus, the LED/laser activation appears to be a good option when using low concentration HP-based agents. In addition, both bleaching protocols did not cause changes on enamel microhardness.
Keywords: Color change; Dental bleaching; Hydrogen peroxide; Laser; LED; Microhardness